Predicting Online Advertisement Avoidance for the Google Ads System Selected Antecedents and Outcome - Laila Refiana Said; Muhammad Hendardi Adinata (Politeknik APP Jakarta, 2024)
Indonesia is the third-largest country that utilizes ad-blockers, despite online advertising there expanding quickly. In addition to consumers generally viewing internet use as common. This study aimed to examine how prior bad experiences and perceived goal impediments affect online advertisement avoidance. Students who used the internet the most during the Covid-19 pandemic in 2021 were chosen as research participants. The F-test demonstrated that perceived aim hindrance, advertisement clutter, and prior terrible experience all impacted advertisement avoidance simultaneously using the Partial Least Square - Structural Equation Modeling (PLS-SEM) technique. The results are anticipated to guide marketing professionals and businesses in choosing how to develop and arrange adverts that are precisely on target without upsetting internet users. The results of this study should help policymakers assess how to create a welcoming and secure online environment.